Host-Plant Resistance and Management of Bacterial Spot of Pepper - Ken Pernezny; Jeff Jones; Russell Nagata; Nikol Havranek (EDIS)
PP-255, a 3-page illustrated fact sheet by Ken Pernezny, Jeff Jones, Russell Nagata, and Nikol Havranek, describes the developments in the campaign to develop cultivars resistant to Xanthomonas euvesicatoria. Published by the UF Department of Plant Pathology, June 2008.